(untitled) (Revista de Crítica Literaria Latinoamericana, 2015)
Since the end of World War 2, continental philosophy has been dominated by Ethics; one of the main authors to consider on this regard is Emmanuel Lévinas. Taking his ethical theory as a point of departure, along with Heideggerian existencialism, in this essay I resent an interpretation of two texts Alejandro Jodovowski’s microfiction, “Misterios del tiempo” and “Después de la Guerra”, which are paradigmatic of his homogeneus microfiction. The main themes are memory, responsibility, and death. This way I am offering an hermeneutical exercise with the aim of establishing the bases towards future studies of this Chilean-French author, taking into consideration both ethics and aesthetics.